Oksidentalisme ; Membuka Kedok Imperalisme Barat: (Studi Politik Imperalisme Belanda Abad 19 dan Awal Abad 20 di Jawa Melalui Kajian Sejarah) - izza, yogi prana (Universitas Nahdlatul Ulama Sunan Giri, 2017)
Occidentalism is the opposite of orientalism. If Orientalism serves as a theory of knowledge that is used to study the eastern world (Islam), then the reverse is occidentalism is used to study the Western world. One of the initiators of Occidentalism figure is Hasan Hanafi. Through his Occidentalism theory, this paper seeks to unmask imperialism Dutch politics in Java in the 19th century and the beginning of 20. The result is a political culture that is used Dutch ancient times, same the patterns with contemporary politics in the present era. Thus, it is time, the reality of contemporary addressed wisely. As the purpose of Occidentalism’s Hassan Hanafi is to awaken people to the project called